Inaplicación del principio de culpabilidad en los procedimientos sancionadores del Tribuna de Contrataciones y la vulneración al debido procedimiento administrativo. - Jimenez Ruiz, Marlene Susana (2023)
The Peruvian administrative system included in our legal system the principle of guilt with Legislative Decree No. 1272, which was promulgated on 12-21-2016, which modified Law No. 27444. In this sense, the objective was to This investigation analyzes the non-application of the principle of guilt in the sanctioning procedures of the Contracting Court in the period 2020-2021 and, consequently, the violation of due administrative procedure. The present investigation concludes that the non-application of the principle of guilt in the infractions of literals i) and j) of art.50 literal 50.1 of the administrative sanctioning procedures of the State Procurement Court violates due dministrative procedure, since it denies the possibility of exempt the infringing conduct of the companies when the fact that there is no subjective responsibility (intent or negligence) is invoked, thus violating the right to obtain a reasoned and legally-based decision, by leaving aside the assessment and analysis of the Subjective responsibility and the principles that it implies, thus omitting the application of the minimum guarantees that protect the companies that are immersed in these sanctioning administrative procedures.